Intimate partner violence perpetration, immigration status, and disparities in a community health center-based sample of men. - Gupta, Jhumka; Acevedo-Garcia, Dolores; Hemenway, David; Decker, Michele R; Raj, Anita; Silverman, Jay G (Public health reports (Washington, D.C. : 1974), 2010)
We examined disparities in male perpetration of intimate partner violence (IPV) based on immigration status.
Keywords: Acculturation; Adolescent; Adult; Boston; Community Health Centers; Domestic Violence; Emigrants and Immigrants; Humans; Language; Male; Sexual Partners; Urban Population; Young Adult